2006
DOI: 10.1021/ac0609125
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Switching Accurate Mass Measurement of Pharmaceutical Samples Using Desorption Electrospray Ionization and a Dual Ion Source Interfaced to an Orthogonal Acceleration Time-of-Flight Mass Spectrometer

Abstract: A novel approach for the rapid, accurate mass analysis of pharmaceutical solid, liquid, and cream formulations using desorption electrospray ionization (DESI) is described. The method is based on polarity switching and real-time accurate mass measurement in an orthogonal acceleration time-of-flight mass spectrometer fitted with a dual-inlet electrospray ion source. Infusion of a reference compound into one inlet provides a single-point "lock mass" for accurate mass measurement. The other inlet sprays solvent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…DESI-MS has been rapidly accepted as a very successful tool for the rapid and sensitive analysis of various analytes and different samples, such as pharmaceutical tablets, explosives, polymers, metabolites, proteins, metabolomic samples, intact bacteria, biological tissues imaging and other surfaces. [10][11][12][13][14][15][16][17][18] A recent development for DESI with improved selectivity and efficiency has been accomplished by doping specific reactive reagents in the DESI spray solvent. This allows specific solution-phase ion/molecule chemical reactions between the charged spray microdroplets and surface molecules to occur before the resulting secondary microdroplets are propelled into the mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…DESI-MS has been rapidly accepted as a very successful tool for the rapid and sensitive analysis of various analytes and different samples, such as pharmaceutical tablets, explosives, polymers, metabolites, proteins, metabolomic samples, intact bacteria, biological tissues imaging and other surfaces. [10][11][12][13][14][15][16][17][18] A recent development for DESI with improved selectivity and efficiency has been accomplished by doping specific reactive reagents in the DESI spray solvent. This allows specific solution-phase ion/molecule chemical reactions between the charged spray microdroplets and surface molecules to occur before the resulting secondary microdroplets are propelled into the mass analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] In 2006, Cooks and co-workers found that if the DESI spray was doped with selective chemical reagents, it was possible to perform ion/molecule reactions between the charged microdroplets and an analyte exposed on a solid sample surface. 26 This DESI modality, which was first named as 'reactive' DESI, has proven successful in detecting TATP 27 and other explosives 28 on a variety of surfaces.…”
mentioning
confidence: 99%
“…Various active pharmaceutical ingredients in different pharmaceutical products with the forms of tablet [30,[33][34][35][36][37][38][39][40][41][42][43], capsule [44], ointment [33,35,36,39], eye drop [33], cream [34,43], and gel [35,39,42] as well as a thermal degradation product of loratadine in Claritin tablet [33] were all successfully analyzed by DESI-MS with the strategy of surface desorption/ionization.…”
Section: Desorption Electrospray Ionizationmentioning
confidence: 99%